PENERAPAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 004 TEMBILAHAN KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Muhammad, MH. (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The low yield of fourth grade students learn science SD Negeri 004 Tembilahan this is the background of this research, this is evidenced by the acquisition of the average student learning outcomes that is equal to 63.31. This study aims to improve student learning outcomes through the implementation of the method of administration tasks. This research is a classroom action research subjects fourth graders SD Negeri 004 Tembilahan by the number of 32 students, the study was conducted as much as two cycles consisting of two meetings. The data used in this study focuses on improving learning outcomes and student learning completeness. Based on the results obtained under the data science learning outcomes increased in each cycle, the pre-cycle (basic score) average learning results obtained by the students was 63.31 by the number of students who completed by 16 (50.00%), in cycle I rise to 70.31 by the number of students who pass the number 25 (78.12%), and the second cycle increased to 73.59 by the number of students who completed totaling 32 students. Based on these results, it can be concluded that the application of the method of administration tasks can improve student learning outcomes IPA IV SD Negeri 004 Tembilahan